(untitled) (Journal of Atomic and Molecular Sciences, 2018)
A theoretical analysis is presented for the nonadiabatic photodissociation process of hydrogen fluoride and it deuterated species. Four electronic states X^1Σ^+, a^3Π, A^1Π, and ^3Σ^+ are involved in the studies. Based on the accurate ab initio calculations of the potential energy curves, transition dipole moment and spin-orbit couplings among the accessible states, the time dependent quantum wave packet approach with the split-operator scheme is employed to investigate the dissociative dynamics. The dissociative process is analyzed via the evolution of the wave packets. The total cross sections, partial cross sections and branching fractions for both HF and DF initially excited from the vibrational levels v= 0-3 of the ground state are evaluated. The calculations are compared with the former investigations and present the prediction for a broad range of the incident photon energies.